An integrase toolbox to record gene-expression during plant development - Guiziou, Sarah; Maranas, Cassandra J.; Chu, Jonah C.; Nemhauser, Jennifer L. (Nature communications, 2023)
There are many open questions about the mechanisms that coordinate the dynamic, multicellular behaviors required for organogenesis. Synthetic circuits that can record in vivo signaling networks have been critical in elucidating animal development. Here, we report on the transfer of this technology to plants using orthogonal serine integrases to mediate site-specific and irreversible DNA recombination visualized by switching between fluorescent reporters. When combined with promoters expressed during lateral root initiation, integrases amplify reporter signal and permanently mark all descendants. In addition, we present a suite of methods to tune the threshold for integrase switching, including: RNA/protein degradation tags, a nuclear localization signal, and a split-intein system. These tools improve the robustness of integrase-mediated switching with different promoters and the stability of switching behavior over multiple generations. Although each promoter requires tuning for optimal performance, this integrase toolbox can be used to build history-dependent circuits to decode the order of expression during organogenesis in many contexts. Synthetic circuits that can record in vivo signaling networks is critical in elucidating developmental process. Here, the authors describe the engineering and application of synthetic in vivo recorders with different promoters that can drive spatiotemporally-specific integrase switching during lateral root initiation.